Identification of new SUMO activating enzyme 1 inhibitors using virtual screening and scaffold hopping. Issue 4 (15th February 2016) - Kumar, Ashutosh; Ito, Akihiro; Hirohama, Mikako; Yoshida, Minoru; Zhang, Kam Y.J.
Graphical abstract: Abstract: Sumoylation involves the enzymatic conjugation of small ubiquitin-like modifier (SUMO) protein to their substrate proteins. Sumoylation is not only crucial for maintaining normal cellular physiology but also implicated in the development of several diseases including cancer. SUMO E1, the first protein in sumoylation pathway is of particular significance due to its confirmed role in tumorogenesis. However, notwithstanding its role as potential drug target, only a few small molecule inhibitors of SUMO E1 have been identified. Here, we report the identification of pyrazole and thiazole urea containing compounds as inhibitors of SUMO E1. We have utilized 3D-shape matching, electrostatic potential similarity evaluations and molecular docking to scaffold hop from previously known aryl urea scaffold with SUMO E1 activity to thiazole and pyrazole urea based scaffolds. These two classes of compounds were found to have moderate SUMO E1 inhibitory activity and can be used as starting points for the development of highly potent lead compounds against cancer.